2022
DOI: 10.30598/pejlac.v2.i1.pp109-116
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Self Organized Learning Environment (SOLE) Learning Model on Learning Outcomes of German Language Teaching Planning Course

Abstract: The implementation of Distance Learning (PJJ), carried out at the German Language Education Study Program at Pattimura University, is inseparable from various obstacles that hinder the lecture process, one of which is the learning outcomes obtained by students. This study is quasi-experimental quantitative research, namely One-Group Pretest-Posttest, to test the effect of the application of the Self Organized Learning Environment (SOLE) learning model on student learning outcomes in the German Language Teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The steps of quantitative research methods as primary methods and qualitative research methods as secondary methods are shown in Figure 2 (Rusilowati et al, 2021). The experimental design used in the study is the One-Group Pretest-Posttest Design, where researchers can determine whether there is an influence by comparing students' abilities before and after the study effect by comparing students' abilities before and after being given treatment (Marantika et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The steps of quantitative research methods as primary methods and qualitative research methods as secondary methods are shown in Figure 2 (Rusilowati et al, 2021). The experimental design used in the study is the One-Group Pretest-Posttest Design, where researchers can determine whether there is an influence by comparing students' abilities before and after the study effect by comparing students' abilities before and after being given treatment (Marantika et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…the effectiveness of character value-based differentiation learning R&D (Marantika et al, 2023;Nurdini, 2021;Hamad, 2020;Ghazouani, 2018;Demir, 2021b;Bal, 2018;Variacion et al, 2021;Chandra Handa, 2019) The teacher understands the concept and application of differentiated learning well. This approach improves student learning outcomes and motivation.…”
Section: Measured Variablementioning
confidence: 99%
“…By paying attention to student characteristics such as interests, profiles, learning styles, and learning readiness, teachers can provide learning experiences that are more relevant and meaningful to each student. (Alhafiz, 2022;Evendi et al, 2023;Marantika et al, 2023;Rafiska & Susanti, 2023;Saadah, Wastri, Asmendri, & Sari, 2023;Gusteti & Neviyarni, 2022;Wahyuni, 2022). This allows students to learn in a level of difficulty that suits their abilities, so they can develop a better understanding and master the material more effectively.…”
Section: Impact Of Differentiated Learning On Student Learning Outcomesmentioning
confidence: 99%